Optimization of Statistical Estimation of Half-Hour Load Maximum of Industrial Enterprise - V. A. Anischenko; V. V. Belko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2009)
The paper considers a problem pertaining to determination of a statistical estimation of the half-hour load maximum of an industrial enterprise on the criterion of a minimum of total expenses. The estimation is made on the basis of fractile optimization characterizing a corridor width of value uncertainty of the half-hour load